Systematic review of evidence-based guidelines on medication therapy for upper respiratory tract infection in children with AGREE instrument. - Linan Zeng; Lingli Zhang; Zhiqiang Hu; Emily A Ehle; Yuan Chen; Lili Liu; Min Chen (PLoS ONE)
Objectives To summarize recommendations of existing guidelines on the treatment of upper respiratory tract infections (URTIs) in children, and to assess the methodological quality of these guidelines. Methods We searched seven databases and web sites of relevant academic agencies. Evidence-based guidelines on pediatric URTIs were included. AGREE II was used to assess the quality of these guidelines. Two researchers selected guidelines independently and extracted information on publication years, institutions, target populations, recommendations, quality of evidence, and strength of recommendations. We compared the similarities and differences of recommendations and their strength. We also analyzed the reasons for variation. Results Thirteen guidelines meeting our inclusion criteria were included. Huge differences existed among these 13 guidelines concerning the categorization of evidence and recommendations. Nearly all of these guidelines lacked the sufficient involvement of stake holders. Further, the applicability of these guidelines still needs to be improved. In terms of recommendations, penicillin and amoxicillin were suggested for group A streptococcal pharyngitis. Amoxicillin and amoxicillin-clavulanate were recommended for acute bacterial rhinosinusitis (ABRS). An observation of 2-3 days prior to antibiotic therapy initiation for mild acute otitis media (AOM) was recommended with amoxicillin as the suggested first choice agent. Direct evidence to support strong recommendations on the therapy for influenza is still lacking. In addition, the antimicrobial durations for pharyngitis and ABRS were still controversial. No consensus was reached for the onset of antibiotics for ABRS in children. Conclusions Future guidelines should use a consistent grading system for the quality of evidence and strength of recommendations. More effort needs to be paid to seek the preference of stake holders and to improve the applicability of guidelines. Further, there are still areas in pediatric URTIs that need more research.